Development of a Baby Surveillance System using Video Processing - Rattanachu, Chonthisa; Senglae, Nurida; Ruesa, Nasreeyah; Ruangkarn, Rachata (Princess of Naradhiwas University Journal, 2021)
This research developed a baby surveillance system in a crib bed aiming to detect normal or abnormal movements of baby especially actions that may cause accidents to young children. The system can automatically interpret gestures in the specified areas, which keep an eye on the safety of the child in bedroom. The system using video processing can analyze video frames to detect children behaviors. For example, if a baby is climbing then the system will alert parents. The method of baby surveillance system consists of taking an input video of a baby to use in the system, zoning specific areas on video and eliminating image noises. The following steps are detecting the movements of the child by using the optical flow and analyzing the movements of baby with flow and direction. The system is implemented on OPENCV library and evaluated with video from single-view stationary camera, which is a single view. For the experiment, we used 10 videos of real events at home from the YouTube website. In the videos, a baby was in the cage bed and had normal movements such as climbs and falls. Each video had different environment. The experimental results showed that the baby monitoring system can analyze normal postures, climbing and falling postures with an accuracy of 80.7%.